Advanced load frequency control design approaches for a power system with penetration of renewable energy sources - Wang, Huanzhi (Nanyang Technological University, 2021)
Due to the boost of power systems interconnection as well as penetration of renewable energy (RE) power generation, the loads are varying dynamically. So there is a need of control of system frequency. The major objective of this thesis is aimed at advanced load frequency control (LFC) design approaches for a power system with penetration of RE power generation.